Investigating Students` Competencies of English through Online Learning: Does It Jeopardize Students` Psychological Needs? - Indrawati; Halfiziya, Heleni (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
Covid-19 pandemic has totally transformed how teaching and learning implemented in the classroom. It urged the teachers to use technology in their learning. It’s not only about moving the offline class to the screen-tech class but it’s more about the capability of delivering the lesson through online platforms, such as Google Classroom. In fact, the problems encountered by teachers and learners are very complexed. It deals with the internet connection, teachers’ competencies in using the online platform, proper gadget, and students’ difficulties in customizing themselves to a new learning era. The latest is indeed affect their psychological need; their learning anxiety increased and some factors might influence the effectiveness of learning itself.  This study discussed how anxiety in learning can be a significant issue in creating a cozy learning atmosphere which is barely needed in making meaningful instructions